(untitled) (Research, Society and Development, 2020)
This study aimed to conduct a theoretical-practical reflection on the performance of the multidisciplinary team in the health residency for a patient affected with pemphigus vegetans in the hospital. It is a descriptive study, with a qualitative approach, of the experience report type, about the multiprofessional assistance provided to a patient with vegetative pemphigus. Thus, mention is made of nursing, physiotherapy and psychology to the multidisciplinary care of a patient hospitalized for investigation of a disease, in which the clinical diagnosis of vegetative pemphigus is concluded. Thus, the residents’ experience reflected on the need for adequate support for the care of this patient, highlighting the importance of listening and a holistic view in promoting humanized care through the dialogue between professionals and the theoretical apparatus. Thus, the report points out the importance of comprehensive and humanized care that has a multidirectional approach and representation for future research.